Sex differences in intracranial plaque burden in patients with type 2 diabetes mellitus with acute ischemic cerebrovascular disease: a pilot study based on high-resolution MRI - Yan, Xuejiao; Li, Ling; Gao, Jie; Wang, Lihui; Ai, Kai; Lei, Xiaoyan; Tang, Min; Zhang, Xiaoling; Zhang, Dongsheng (Frontiers in Endocrinology, 2025)
BackgroundAtherosclerosis (AS) is the main cause of macrovascular disease. Previous studies have found sex differences in the prevalence of type 2 diabetes mellitus (T2DM) and its associated macrovascular disease outcomes. However, the relationship between sex differences, T2DM, and AS is not fully understood. This study attempts to explore possible associations between sex, treatment, and the burden of intracranial atherosclerosis (ICAS) in patients with T2DM who have experienced an acute ischemic cerebrovascular disease.MethodsWe focused on patients with T2DM with acute ischemic stroke or transient ischemic attack due to intracranial atherosclerotic stenosis. ICAS was assessed by 3T cardiovascular magnetic resonance vascular wall imaging. Plaque counts of the total, proximal, and distal intracranial arteries were used to assess plaque burden. Patients with a history of T2DM and currently taking hypoglycemic drugs were defined as being treated. Poisson regression models or negative binomial regression models were used to analyze the interaction between sex and treatment in relation to plaque burden.ResultsA total of 495 plaques were detected in 120 patients (75 male; mean age, 60.77 ± 11.01 years), including 311 proximal and 184 distal plaques. The intracranial culprit plaque was located proximal to the artery in both male (85.3%) and female (88.9%) patients. The adjusted total and proximal intracranial plaque burdens were 1.261 times (95% confidence interval [CI], 1.050–1.515, P=0.013) and 1.322 times (95%CI, 1.055–1.682, P=0.016) higher in male than in female patients. The risk ratio for proximal plaque burden in untreated male versus female patients was 0.966 (95%CI, 0.704–1.769). However, the proximal plaque risk ratio for treated male versus female patients was 1.530 (95%CI, 1.076–2.174). The interaction of sex and treatment significantly affected the proximal plaque burden.ConclusionMale patients with T2DM and acute cerebrovascular disease have a significantly higher adjusted risk of total and proximal intracranial plaque burden compared to female patients. Female patients undergoing antidiabetic treatment have a significantly reduced risk of proximal plaque to males. Considering that culprit plaques tend to accumulate in the proximal arteries, understanding how to reduce the burden of proximal plaques may help reduce the risk of adverse cerebrovascular events.